Bacterial Resistance Test to Antibiotics Through Throat Swab Specimens of Children with Acute Respiratory Tract Infections (ARIs) - Nurdin, Erpi; Zuchrullah, Mukhtasyam; Halik, Sofyanti Abdul (Jurnal Analis Medika Biosains (JAMBS), 2025)
Acute Respiratory Infections (ARIs) are contagious diseases that affect the respiratory tract and remain a leading cause of morbidity and mortality, particularly among children. The use of antibiotics without proper sensitivity testing can lead to bacterial resistance; therefore, research is needed to determine the effectiveness of commonly prescribed antibiotics. ARIs is one of the primary causes of morbidity and mortality, especially in children in developing countries. The irrational use of antibiotics or the absence of adequate sensitivity testing is one of the main factors contributing to the rise in bacterial resistance, which may reduce the effectiveness of treatment and increase the public health burden. Objective to determine the sensitivity levels of several types of antibiotics against bacteria that cause ARIs, obtained from throat swab specimens of children with ARIs in several community health centers (Puskesmas) under the Ternate City Health Office. This study is a descriptive research using a laboratory approach, applying the Kirby-Bauer method for antibiotic sensitivity testing against bacteria using Mueller Hinton Agar (MHA) media. Bacterial identification showed a predominance of Staphylococcus epidermidis (45%), followed by Streptococcus pneumoniae (35%), and Streptococcus pyogenes (20%). Sensitivity testing revealed that Streptococcus pneumoniae was most sensitive to gentamicin (100%), while Staphylococcus epidermidis showed high sensitivity to ciprofloxacin (100%). On the other hand, cefixime exhibited the highest level of resistance. Sensitivity testing is crucial before administering antibiotics to prevent resistance and ensure appropriate treatment for children with ARIs.